Moderating Analpysis of the Audit Committee on the Effect of Auditor Workload, Audit Tenure, and Auditor Specialization on Audit Quality - Ferry Adang; Amin Wijoyo; Steven Wiryajaya; Richard Edbert (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study is motivated by the importance of audit quality in ensuring the credibility of financial statements, particularly in the property and real estate sector, where complex transactions often increase audit risk. The objective of this research is to obtain empirical evidence on the effect of auditor workload, audit tenure, and auditor specialization on audit quality, with the audit committee acting as a moderating variable. This study employs a quantitative approach using secondary data derived from annual reports and audited financial statements of companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The sampling technique used is purposive sampling, resulting in 213 companies that meet the specified criteria. Data processing was conducted using Microsoft Excel, while hypothesis testing and statistical analysis were performed using E-Views 10. The results indicate that auditor workload, audit tenure, and auditor specialization have significant effects on audit quality, and the audit committee is able to moderate these relationships, thereby strengthening the influence of independent variables on audit quality. In conclusion, this study confirms that both auditor-related factors and corporate governance mechanisms play a vital role in improving audit quality, and the presence of an effective audit committee enhances oversight effectiveness and contributes to higher-quality financial reporting.